Balanced and unbalanced translocations in a multicentric series of 2843 patients with chronic lymphocytic leukemia. Issue 1 (4th September 2021) - Costa, Dolors; Granada, Isabel; Espinet, Blanca; Collado, Rosa; Ruiz‐Xivillé, Neus; Puiggros, Anna; Uribe, Marisol; Arias, Amparo; Gómez, Cándida; Delgado, Julio; Pereira, Arturo; Magnano, Laura; et al.
Abstract: Chromosomal translocations in chronic lymphocytic leukemia (CLL) are very rare, and therefore systematic analysis of large series of cases is needed to allow the identification of recurrent rearrangements, breakpoints involved, and target genes. The aims of the present study were to identify new translocations and their clinical impact and to establish their frequency in a large cohort of 2843 CLL patients. By conventional cytogenetics 250 translocations were identified in 215 (7.5%) patients, 186 (74%) were apparently balanced and 64 (26%) were unbalanced. All chromosomes were involved in translocations, except Y chromosome. The chromosomes more frequently translocated were in decreasing frequency chromosomes 14, 18, 13, 17, 1, 6, 2, 3, 8, and 11. Translocations were found in the karyotypes either as the unique chromosomal abnormality (27%), associated with another alteration (24%), or as a part of a complex karyotype (CK, 48%). A large proportion of rearranged breakpoints involved genes related to CLL such as IGH (14q32), RB1, MIR15A, MIR16‐1 (13q14), BCL2 (18q21), IGL (22q11.2), TP53 (17p13), IRF4 (6p25‐p23), ATM (11q22), and CDK6 (7q21). Overall, 76 novel CLL translocations were identified, including a recurrent t(8;11)(p21;q21‐23). Whole‐genome sequencing and/or copy‐number microarray data of 24 cases with translocations confirmed all rearrangements, enabled refinement of 3 karyotypes and all breakpoints at gene level. The projected survival and time to first treatment significantly decreased linearly with the number of translocations. In summary, this study allowed to establish the frequency of translocations (7.5%) and to identify new translocations in a cohort of 2843 CLL patients.